The Claudin Family Protein FigA Mediates Ca2+ Homeostasis in Response to Extracellular Stimuli in Aspergillus nidulans and Aspergillus fumigatus - Qian, Hui; Chen, Qiuyi; Zhang, Shizhu; Lu, Ling (Frontiers in Microbiology, 2018)
The claudin family protein Fig1 is a unique fungal protein that is involved in pheromone-induced calcium influx and membrane fusion during the mating of Saccharomyces cerevisiae and Candida albicans. Whether and how Fig1 regulates Ca2+ homeostasis in response to extracellular stimuli is poorly understood. Previously, we found Aspergillus nidulans FigA, a homolog of Fig1 in S. cerevisiae, similar to the high-affinity calcium uptake system (HACS), is required for normal growth under low-Ca2+ minimal medium. In this study, using the calcium-sensitive photoprotein aequorin to monitor cytosolic free calcium concentration ([Ca2+]c) in living cells, we found that the FigA dysfunction decreases the transient [Ca2+]c induced by a high extracellular calcium stress. Furthermore, FigA acts synergistically with CchA (a high-affinity Ca2+ channel) to coordinate cytoplasmic Ca2+ influx in response to an extracellular Ca2+ stimulus. Moreover, FigA mediates ER stress-induced transient [Ca2+]c in the presence or absence of extracellular calcium. Most importantly, these [Ca2+]c responses mediated by FigA are closely related to its conserved claudin superfamily motif, which is also required for hyphal growth and asexual development in A. nidulans. Finally, the function of FigA in Aspergillus fumigatus, the most common airborne human fungal pathogen was studied. The result showed that the two FigA homologous in A. nidulans and A. fumigatus have a large degree of functional homology not only in asexual development but also in regulating transient [Ca2+]c. Our study expands the knowledge of claudin family protein FigA in Ca2+ homeostasis in response to extracellular stimuli.